Can Innovative Technologies Overcome HbA1c Disparity for African-American Youth with Type 1 Diabetes?. (September 2021) - Chalew, Stuart; Delamater, Alan M.; Washington, Sonja; Bhat, Jayalakshmi; Franz, Diane; Gomez, Ricardo; Felipe, Dania; Tieh, Peter; Finger, Laurie
Achieving normal or near-normal glycemic control as reflected by HbA1c levels in patients with type 1 diabetes (T1D) is important for preventing the development and progression of chronic complications. Despite delineation and dissemination of HbA1c management targets and advances in insulin pharmacology, insulin delivery systems, and glucose monitoring, the majority of children with T1D do not achieve HbA1c goals. In particular, African Americans are more likely not to reach HbA1c goals and have persistently higher HbA1c than Non-Hispanic Whites. Availability of pumps and other technology has not eliminated the disparity in HbA1c. Multiple factors play a role in the persisting racial disparity in HbA1c outcome. The carefully designed application and deployment of new technology to help the patient/family and facilitate the supportive role of the diabetes management team may be able to overcome racial disparity in glycemic outcome and improve patient quality of life.